New DSH planetary nebulae and candidates from optical and infrared surveys. Issue 7 (July 2016) - Kronberger, Matthias; Parker, Quentin A; Jacoby, George H; Acker, Agnes; Alves, Filipe; Bojicic, Ivan; Eigenthaler, Paul; Frew, David J; Harmer, Dianne; Patchick, Dana; Reid, Warren; Schedler, Johannes
Abstract: To date, the planetary nebula (PN) survey of the Deep Sky Hunters collaboration has led to the detection of more than 250 previously unknown candidate planetary nebulae (PNe). About 60% of them were found during the past two years and are expected to be true, likely or possible PNe because careful vetting has already thrown out more doubtful objects. The majority of the new PN candidates are located within the boundaries of the SHS and IPHAS Ha surveys and were discovered by combining MIR data from the WideField Infrared Survey Explorer (WISE) with optical data from the IPHAS, SHS and DSS surveys, and UV data from the Galaxy Evolution Explorer(GALEX).